Complete search strategies for “ACE-ing Healthcare: Healthcare Utilization from Emerging to Older Adulthood in Individuals with Adverse Childhood Experiences (ACEs): A Systematized Literature Review” Wilson, L. - Forbes, Carrie S. (My University, 2025)
The concept domains for this search included: emerging adults and adults in the age range of (20-63); adverse childhood experiences or ACEs; healthcare utilization. Searches were performed in June 2025. Databases included: PsycINFO via ProQuest, MEDLINE via PubMed, CINAHL via EBSCOhost, Education Database via ProQuest, and SOCIndex via EBSCOhost. There were no limiters used in this search.
Keywords: Emerging adults and adults in the age range of (20-63); adverse childhood experiences; ACEs; healthcare utilization: systematized review